Wave-absorbing material based on reduction and nitridation modification of fly ash magnetic separation product and preparation method of wave-absorbing material

By nitriding modification of fly ash magnetic separation products, the matching thickness and impedance matching problems of Fe3O4 materials in electromagnetic wave absorption are solved, and the electromagnetic parameters changes and absorption performance of the wave absorbing material are achieved.

CN119822335APending Publication Date: 2025-04-15CHINA JILIANG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510016034.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

As an electromagnetic wave absorbing material, Fe3O4 has problems with large matching thickness, large density and poor impedance matching, and it is difficult to meet the requirements of low matching thickness, light weight, wide effective absorption bandwidth and high reflection loss absorption capacity at the same time.

Method used

By nitriding and modifying the fly ash magnetic separation product, the specific steps include nitriding the fly ash reduction product using ammonia at 500°C, and adjusting the nitriding time to obtain an absorbing material with a high Fe3N content.

Benefits of technology

The electromagnetic parameters of the absorbing material are changed, the matching thickness is reduced, and the absorption performance is improved. The optimal reflection loss value of the 5-h nitrided sample is -23.08dB, the effective absorption bandwidth is 10.08~12.08GHz, and the matching thickness is 4mm.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119822335A_ABST
    Figure CN119822335A_ABST
Patent Text Reader

Abstract

The invention discloses a wave-absorbing material based on reduction and nitridation modification of a fly ash magnetic separation product and a preparation method of the wave-absorbing material, and belongs to the technical field of preparation of wave-absorbing materials. The preparation method of the wave-absorbing material based on reduction and nitridation modification of the fly ash magnetic separation product comprises the following steps: carrying out nitridation modification on a fly ash reduction product by adopting ammonia gas at 500 DEG C to obtain the wave-absorbing material based on reduction and nitridation modification of the fly ash magnetic separation product. According to the method, the nitridation time is changed to explore the influence of the nitridation degree on the crystal structure, the surface appearance, the magnetic performance and the electromagnetic wave absorbing characteristic of a nitridation system sample, and the strongest reflection loss value of the nitridation sample at 11.28 GHz within 5 hours is-23.08 dB; the effective absorption bandwidth is 10.08 to 12.08 GHz, and the matching thickness is 4mm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of preparation of wave-absorbing materials, and in particular relates to a wave-absorbing material based on reduction and nitridation modification of fly ash magnetic separation products and a preparation method thereof. Background Art

[0002] In recent years, with the rapid development of microwave communications, computers and other portable electronic devices, electromagnetic radiation pollution and electromagnetic wave interference have continued to affect residents' lives. In order to solve this problem, researchers are working hard to develop a high-efficiency microwave absorbing material that has both high microwave absorption efficiency and low thickness.

[0003] As a kind of magnetic material, Fe3O4 has the characteristics of high magnetic permeability, high magnetic loss, high saturation magnetization and good stability, and has a good future in electromagnetic wave absorption. In terms of wave absorption performance, the loss of Fe3O4 to electromagnetic waves includes conductivity loss, ion polarization loss in dielectric loss, natural resonance loss, domain wall resonance loss and exchange resonance loss in magnetic loss. The characteristics of multiple loss mechanisms have also attracted the interest of many researchers in Fe3O4 as an electromagnetic wave absorption material. However, Fe3O4 also has its common disadvantages as a ferrite, namely, large matching thickness and high density, Snoek limit and poor impedance matching, so it is difficult to simultaneously meet the requirements of low matching thickness, light weight, wide effective absorption bandwidth and high reflection loss absorption capacity.

[0004] Therefore, in order to improve the electromagnetic absorbing ability of Fe3O4 and meet the current demand for absorbing materials, it is necessary to adjust the parameters of Fe3O4 itself and modify the fly ash reduction product to obtain a new type of absorbing material. Summary of the invention

[0005] In order to solve the above technical problems, the present invention proposes a wave absorbing material based on reduction and nitridation modification of fly ash magnetic separation products and a preparation method thereof.

[0006] To achieve the above object, the present invention provides the following technical solutions:

[0007] One of the technical solutions of the present invention:

[0008] A method for preparing a wave absorbing material based on reduction nitridation modification of fly ash magnetic separation products, comprising the following steps:

[0009] At 500° C., ammonia is used to perform nitridation modification on the fly ash reduction product to obtain the absorbing material based on the fly ash magnetic separation product reduction nitridation modification.

[0010] Optionally, the time during the nitridation modification process is 1-5 hours.

[0011] Furthermore, the time during the nitriding modification process is 5 hours.

[0012] Optionally, the flow rate of the ammonia gas is 150 sccm.

[0013] Optionally, the preparation method of the fly ash reduction product is:

[0014] The fly ash is subjected to magnetic separation and hydrogen reduction in sequence to obtain the fly ash reduction product.

[0015] Furthermore, the magnetic separation adopts a pull-out dry magnetic separation, and the magnetic separation product is obtained after 31 separation rings are magnetically separated;

[0016] The reduction temperature in the hydrogen reduction process is 550° C. and the reduction time is 3 hours.

[0017] The second technical solution of the present invention:

[0018] A wave absorbing material based on reduction and nitridation modification of fly ash magnetic separation products is prepared by the above preparation method.

[0019] Optionally, the particle size of the absorbing material is 5 to 50 μm.

[0020] Optionally, the strongest reflection loss value of the absorbing material at 11.28 GHz is -23.08 dB; the effective absorption bandwidth is 10.08 to 12.08 GHz, and the matching thickness is 4 mm;

[0021] At an operating frequency of 18 GHz, the effective absorption bandwidth matching thickness of the 5h sample can reach 1.5 mm.

[0022] Compared with the prior art, the present invention has the following advantages and technical effects:

[0023] The present invention performs nitridation modification on the 550°C, 3h hydrogen reduction sample by adjusting the nitridation time within the range of 1 to 5h. The XRD and SEM results show that the nitrided sample contains Fe3N. The electromagnetic parameters of the nitrided sample change significantly. According to the reflection loss spectrum, the matching thickness corresponding to the optimal RL value of the nitrided sample decreases. The optimal RL value of the 5h nitrided sample is -23.08dB, and the effective absorption bandwidth is 10.08 to 12.08GHz at 11.28GHz, and the matching thickness is 4mm. 5h ammonia nitridation is the optimal solution for the material to obtain good wave absorbing performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:

[0025] Figure 1 This is a physical picture of the magnetic rod housing with a separation ring of the pull-out dry magnetic separation device of the present invention;

[0026] Figure 2 It is a schematic diagram of the working principle of the pull-type dry magnetic separation device of the present invention;

[0027] Figure 3 The XRD patterns of (a) the 5h nitridation sample and (b) the 1h to 5h temperature change sample of the present invention;

[0028] Figure 4 This is a SEM image of the reduced sample after nitridation treatment of the present invention;

[0029] Figure 5 XPS spectra of (a) Fe 2p and (b) N 1s of the 5h nitrided sample of the present invention;

[0030] Figure 6 Magnetic hysteresis loops of samples with different nitriding times of the present invention;

[0031] Figure 7 (a) dielectric real part, (b) dielectric imaginary part, (c) magnetic permeability real part, (d) magnetic permeability imaginary part of the samples of the present invention with different nitridation time at 2 to 18 GHz;

[0032] Figure 8 The (a) dielectric loss tangent and (b) magnetic loss tangent spectra of the reduction product of the present invention at different nitridation times at 2 to 18 GHz;

[0033] Fig. 9 It is a three-dimensional surface diagram of the reflection loss value of (a) magnetic separation product, (b) 1h, (c) 2h, and (d) 5h nitrided samples of the present invention at different thicknesses as a function of frequency;

[0034] Fig.10 It is the quarter-wavelength theoretical matching thickness, reflection loss and normalized impedance matching curve of the 5h nitrided sample of the present invention. DETAILED DESCRIPTION

[0035] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0036] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0037] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0038] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.

[0039] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0040] The chemical composition and corresponding content (measured by XRF) of the fly ash used in the present invention are shown in Table 1 below.

[0041] Table 1 Chemical composition and corresponding content of fly ash

[0042]

[0043] Example 1

[0044] A method for preparing a microwave absorbing material based on fly ash reduction products comprises the following steps:

[0045] (1) Magnetic separation of fly ash. The specific operation is: slowly pour the fly ash into the self-made dry magnetic separation equipment at a uniform speed for magnetic separation, and collect the product at the discharge port, which is called the magnetic product. The gray-white powder obtained at the tailings port is the tailings.

[0046] The self-made dry magnetic separation equipment (reference patent CN 116328937 A) consists of a magnetic rod and a non-magnetic shell, on which 31 separation rings with a height of 3 mm and a width of 7 mm are arranged. Figure 1As shown. The separation ring is in a circular shape, and its function is to promote the relative movement of the magnetic and non-magnetic components in the entrained clusters to achieve effective separation. When the device is used for experiment, a quantitative sample is poured onto the separation ring of the device, and the sample is magnetically separated by 31 separation rings to obtain a magnetic separation product. The product mass, the iron oxide content in the product, and the iron recovery rate are calculated. The specific working principle of magnetic separation is: at the beginning of magnetic separation, Figure 2 As shown in position A in the figure, fly ash enters the magnetic separation device from the feed port, and the magnetic particles are attracted by the magnetic rod and adsorbed on the surface of the magnetic rod. At the same time, after the magnetic particles are magnetized by the magnetic rod, they can be regarded as small magnets, which interact magnetically with each other to form dense clusters. When clusters are formed, non-magnetic particles are entrained by adjacent magnetic particles, are also mixed in the clusters, and are adsorbed on the surface of the magnetic rod. As the clusters move to the right with the magnetic rod, the magnetic particles continuously jump over the separation ring, and the non-magnetic particles in the clusters continuously fall off. When the magnetic rod is pulled to position C, the non-magnetic particles basically disappear, and the magnetic particles are blocked by the baffle on the port, and fall to the discharge port under the action of their own gravity, and finally complete the dry magnetic separation; the results of magnetic separation (two parallel tests) are shown in Table 2:

[0047] Table 2

[0048]

[0049] (2) Reduction of magnetic separation products: The magnetic separation products were placed in a TF55030A tubular furnace, and the temperature was raised to a target temperature of 550°C under argon protection. Then, the temperature was kept for reduction for 3 hours in a pure hydrogen atmosphere at a flow rate of 20 sccm. Then, the furnace was cooled to room temperature under argon protection to obtain a reduced product.

[0050] (3) Nitriding of the reduction product: The product after hydrogen reduction was placed in a Lindberg / Blue tube furnace and heated to 500°C under an argon protective atmosphere. The temperature was kept at 1 h, 2 h and 5 h respectively under an ammonia flow rate of 150 sccm. The nitrided product was then cooled to room temperature in an argon atmosphere to obtain a nitrided product mainly composed of Fe3N.

[0051] Effect verification

[0052] 1. Morphological characterization of nitrided samples

[0053] The magnetic separation product was first reduced with hydrogen at 550°C for 3 h and then nitrided in an ammonia atmosphere. Figure 3The graphs of the structure analysis of samples with different reduction times using XRD. It can be found from the figure that the characteristic peaks of the samples after nitridation are consistent, and the products after nitridation of the samples are mainly Fe3N. Characteristic peaks are found at 38.1°, 40.8°, 43.4° and 68.8°. The corresponding crystal planes of Fe3N are (110), (002), (111) and (300) diffraction planes. The corresponding standard PDF card is PDF#97-009-3175 of hexagonal Fe3N, indicating that Fe3N has been successfully prepared. In addition, a small amount of SiO2 and Fe3O4 are still found in the samples after nitridation. As the nitridation time increases, the proportion gradually decreases. This is due to the gradual increase of the content of Fe3N with the extension of the nitridation time. It can also be found from the XRD spectrum that the Fe3N diffraction peaks of all samples are clear and obvious, and there is no "mantou peak", indicating that the sample has a good degree of crystallization.

[0054] The sample obtained by nitridation was scanned by SEM, and the scanning results are as follows Figure 4 As shown. After 5 hours of nitridation, the size of the sample has no significant change compared with the magnetic separation product. Most of the particles are complete spheres, and there are differences in the size of each particle. The overall particle size is distributed within 5-50μm; and some particles are observed to have holes and incompleteness. The surface of the sample particles after nitridation is rougher than that of the magnetic separation product. This is because during the nitridation process of the sample, a large number of ε phase nuclei exist on the surface of the sample; these nuclei are polyhedral, and during the growth process, their growth rates are different, the anisotropy of the ε phase diffusion is obvious, the grains grow, and a rough shell is formed on the surface.

[0055] Figure 5 It is the XPS spectrum of Fe 2p and N1s of the 5h nitrided sample. Figure 5 (a) shows that the peak measured at ~712 eV can be attributed to the peaks at 710.34 eV, 712.06 eV, 713.65 eV, and 715.87 eV, which are attributed to Fe element, Fe 2+ , Fe 3+ and satellite peaks; in addition, another satellite peak was observed near ~720 eV; the peak observed near ~725 eV was attributed to Fe 3+ (727.42eV) and Fe 2+ (722.81eV), the XPS spectrum results prove that there is a small amount of Fe in the sample. Figure 5 As can be seen in (b), the N 1s peak can be divided into the peak of Pyridinic-N (397.21 eV) and the peak of Fe-N bond (399.49 eV).

[0056] 2. Magnetic properties analysis of nitrided samples

[0057] For the magnetic property test of the samples, the present invention uses a vibrating sample magnetometer, and adds a changing magnetic field within a range of -10000 Gs to 10000 Gs outside all the test samples to obtain the hysteresis loop of the test samples. Figure 6 is the hysteresis loop of the 1h, 2h, and 5h samples, and its M S 、M r and H C As shown in Table 3. According to the results in the figure and table, after nitriding treatment, the saturation magnetization intensity M of all samples S Gradually increase, 5h sample M S The value is 49.58emu / g; the residual magnetization intensity M r and coercivity H C The M of the 2h sample and the 5h sample increased significantly compared with the magnetic separation product samples. r and H C Since the basic material of nitridation is a multi-component sample of Fe3O4 and Fe, part of Fe3O4 will be reduced by ammonia and then nitrided to form Fe3N. The saturation magnetization intensity M of Fe3N is S It is significantly better than Fe3O4 S Therefore, with the increase of nitriding time, the saturation magnetization intensity of the sample gradually increases. And the M S The results are lower than those of the samples with higher Fe content after reduction at 800℃. This is because the M S Lower than Fe. M of the sample after long-term nitridation r and H C They are all superior to the reduced samples with high Fe content, proving that it can be used as a soft magnetic material with good performance.

[0058] Table 3 Magnetic properties of samples with different nitriding time

[0059]

[0060]

[0061] 3. Analysis of electromagnetic properties of nitrided samples

[0062] In order to analyze the electromagnetic wave absorption performance of Fe3N nitrided samples, the electromagnetic parameters of 1h, 2h and 5h nitrided samples in the range of 2 to 18 GHz were tested by vector network analyzer. The real part ε' and imaginary part ε" of the complex dielectric constant, the real part μ' and imaginary part μ" of the complex magnetic permeability were generated by comparing with the magnetic separation products. Figure 7As shown. According to the spectrum, it can be found that the real part of the complex dielectric constant of the nitrided samples is higher than that of the magnetic separation product samples, and with the increase of nitriding time, ε' shows a gradual decrease trend in the low frequency range, and its peak gradually moves to the high frequency. The ε" of the nitrided samples is negative in the range of 2 to 6 GHz, and the ε" value increases after the nitriding time is extended; the dielectric relaxation peak appears in the range of 14 GHz to 18 GHz, and the peak value increases with the increase of Fe3N content. In the range of 2 to 4 GHz, the real part of the complex magnetic permeability μ' appears negative, and decreases with the nitriding time, and shows a corresponding decreasing trend; the μ' curve generally moves to high frequency with the nitriding time, and in the range of 6 to 18 GHz, the μ' values ​​of each group of samples are relatively small. The μ" initial intensity of the sample with a nitriding time of 5h is the highest, indicating that the sample has the best absorption capacity for electromagnetic waves in the range of 2 to 6 GHz, and the intensity attenuation is obvious; the μ" initial intensity of the sample with a shorter nitriding time is slightly lower, but it is significantly better than the performance of the magnetic separation product, and the μ" of the nitrided sample and the magnetic separation product is similar in the range of 6 to 18 GHz.

[0063] Figure 8 It is the magnetic loss tangent and dielectric loss tangent of the sample of the reduction product under 1-5h nitridation time. Tanδ of the sample after 1h and 2h nitridation ε The decrease in the 2-5 GHz frequency band is obvious and presents a negative value, indicating that the shorter nitridation time eliminates the dielectric loss capacity of the sample in the low frequency band; while the tanδ ε There is a sharp change near the 5.5 GHz frequency, indicating that the loss performance of the sample to electromagnetic waves changes significantly near this frequency. ε Compared with the magnetic separation sample, it is significantly increased, indicating that nitridation will improve the dielectric loss performance of the sample. μ It shows that the magnetic loss performance of the sample to electromagnetic waves varies greatly in the 2-4 GHz frequency band, and with the increase of nitriding time, tanδ μ The amount of change gradually becomes smaller.

[0064] 4. Analysis of microwave absorption performance of nitrided samples

[0065] In order to more clearly compare the effect of nitridation time on the wave absorption performance of the samples, the present invention calculates the reflection loss values ​​of samples of different thicknesses at a frequency of 2-18 GHz by using formulas (1) and (2).

[0066]

[0067] Where: RL represents the reflection loss of the sample; Z in It represents the input impedance when the medium is the sample; Z0 represents the impedance when the medium is air. in It can be obtained from formula 4-2:

[0068]

[0069] Where: Z in represents the input impedance when the medium is a sample; f represents the propagation frequency of the electromagnetic wave; d represents the thickness of the sample; c represents the speed of light; μ r Represents the complex magnetic permeability of the sample; ε r represents the complex dielectric constant of the sample.

[0070] Fig. 9 The three-dimensional surface diagram of the reflection loss value of (a) magnetic separation product, (b) 1h, (c) 2h, and (d) 5h nitrided samples at different thicknesses as a function of frequency. The value below the shaded plane in the figure is less than -10dB, and electromagnetic waves are effectively absorbed within this range. Fig. 9 It can be found that compared with the three-dimensional surface diagram of the magnetic separation product, all the absorption properties of the samples after nitridation are enhanced. The effective absorption bandwidth of the nitrided samples with different matching thicknesses is mainly distributed in the range of 6-12GHz and 16-18GHz, which is wider than the effective absorption bandwidth of the magnetic separation product. In the range of 2-4GHz, the increase in nitridation time cannot make the sample have the ability to absorb electromagnetic waves. With the increase of nitridation time, the difference in the peak value of absorption peak is small, and the peak value is about -25dB. The matching thickness of the effective absorption peak of the nitrided sample is lower than that of the magnetic separation product sample. With the increase of Fe3N content in the sample, the matching thickness of the effective absorption peak gradually decreases; the best RL value of the 5h sample is -23.08dB, which is reached at 11.28GHz, the effective absorption bandwidth is 10.08-12.08GHz, and the matching thickness is 4mm; at the operating frequency of 18GHz, the matching thickness of the effective absorption bandwidth of the 5h sample can reach 1.5mm. After nitridation, the matching thickness of the effective bandwidth is reduced to a certain extent, which broadens the application of the material.

[0071] Since the 5h nitrided sample has good wave absorption and magnetic properties, in order to explore its applicability to the quarter-wavelength theoretical model and impedance matching, the complex magnetic permeability and complex dielectric constant of the 5h nitrided sample are substituted into formulas (3) and (4). The quarter-wavelength theoretical matching thickness, reflection loss and normalized impedance matching curve of the 5h nitrided sample are shown in the figure. Fig.10 shown.

[0072]

[0073] Where: d m is one quarter of the matching thickness of the sample; ε r is the complex dielectric constant of the sample; μ ris the complex magnetic permeability of the sample; f is the propagation frequency of electromagnetic waves; c is the speed of light; n is the matching thickness level (n = 1, 2, 3...). In addition, the normalized impedance matching Z can better evaluate the material's absorption performance of electromagnetic waves, and its formula is as follows:

[0074]

[0075] Where: Z in represents the input impedance when the medium is a sample; Z0 represents the impedance of free space; f represents the propagation frequency of electromagnetic waves; d represents the thickness of the sample; c represents the speed of light; μ r Represents the complex magnetic permeability of the sample; ε r represents the complex dielectric constant of the sample.

[0076] Fig.10 The results show that the theoretical matching thickness level of the 4mm thick sample in the 11GHz range is 7, and the corresponding normalized Z value is close to 1. The Z value curve of the nitrided sample test still shows a downward trend in the range of 17 to 18+GHz, and is close to 1. It is inferred that there is an absorption peak at 18+GHz, and according to the trend of the RL curve, the width of the effective absorption bandwidth corresponding to this absorption peak can be close to 4GHz. The Z value of the sample with lower thickness is much greater than 1 near 6GHz, and the sample has extremely poor wave absorption performance in this frequency band, and even shows an enhancement effect on electromagnetic waves. Therefore, the quarter-wavelength theoretical model and impedance matching theory are also applicable to the analysis of the wave absorption characteristics of nitrided samples.

[0077] In summary, the nitridation time was adjusted within the range of 1 to 5 hours to modify the 550℃, 3h hydrogen reduction sample. The XRD and SEM results showed that the nitrided sample contained Fe3N. The electromagnetic parameters of the nitrided sample changed significantly. According to the reflection loss spectrum, the matching thickness corresponding to the optimal RL value of the nitrided sample decreased. The optimal RL value of the 5h nitrided sample was -23.08dB, and the effective absorption bandwidth was 10.08~12.08GHz at 11.28GHz, with a matching thickness of 4mm. 5h ammonia nitridation is the best solution for the material to obtain good wave absorption performance.

[0078] The above are only preferred specific embodiments of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A method for preparing an absorbing material based on reduction nitridation modification of fly ash magnetic separation products, characterized in that: The following steps are involved: At 500° C., ammonia is used to perform nitridation modification on the fly ash reduction product to obtain the absorbing material based on the fly ash magnetic separation product reduction nitridation modification.

2. The method for preparing a wave absorbing material based on reduction nitridation modification of fly ash magnetic separation products according to claim 1, characterized in that: The time required for the nitridation modification process is 1-5 hours.

3. The method for preparing a wave absorbing material based on reduction nitridation modification of fly ash magnetic separation products according to claim 2, characterized in that: The time required for the nitridation modification process is 5 hours.

4. The method for preparing a wave absorbing material based on reduction nitridation modification of fly ash magnetic separation products according to claim 1, characterized in that: The flow rate of the ammonia gas is 150 sccm.

5. The method for preparing a wave absorbing material based on reduction nitridation modification of fly ash magnetic separation products according to claim 1, characterized in that: The preparation method of the fly ash reduction product is: The fly ash is subjected to magnetic separation and hydrogen reduction in sequence to obtain the fly ash reduction product.

6. The method for preparing a wave absorbing material based on reduction nitridation modification of fly ash magnetic separation products according to claim 5, characterized in that: The magnetic separation adopts dry magnetic separation, and the magnetic separation product is obtained after 31 separation rings. The reduction temperature in the hydrogen reduction process is 550° C. and the reduction time is 3 hours.

7. A wave absorbing material based on reduction and nitridation modification of fly ash magnetic separation products, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 6.

8. The microwave absorbing material based on reduction nitridation modification of fly ash magnetic separation products according to claim 7, characterized in that: The particle size of the wave absorbing material based on reduction and nitridation modification of fly ash magnetic separation products is 5 to 50 μm.

9. The microwave absorbing material based on reduction nitridation modification of fly ash magnetic separation products according to claim 7, characterized in that: The wave absorbing material based on reduction and nitridation modification of fly ash magnetic separation products has a strongest reflection loss value of -23.08 dB at 11.28 GHz, an effective absorption bandwidth of 10.08 to 12.08 GHz, and a matching thickness of 4 mm.